Resistance exerting on human body during swimming - Ang, Randy Rui Bin (2019)
The desire to travel faster through water has been present for as long as aquatic transportation is around due to its many associated benefits. This is no different in today’s context of competitive swimming as well. Developments in this area such as improved stroke techniques as well as better swim suits all serve one ultimate goal, that is, to attain faster lap times. There are numerous ways to move quicker through water, the primary one being the reduction in the amount of resistance(drag) faced by the body. This resistance, whose magnitude is very dependent on the shape of the body, can be broadly categorised into either passive or active drag. Passive drag refers to the resistance experienced by the swimmer as it moves through the water as a rigid body. Active drag, on the other hand, includes the drag experienced due to the propulsion generated by the swimmer. This drag can then be further subdivided into 3 components, namely frictional, pressure and wave drag. This report therefore describes the development of a geometrical human swimmer model to investigate the amount of passive wave drag acting on the human body due to changes in its shape. This human model was generated using a Computer-Aided Engineering (CAE) software known as SOLIDWORKS. In the development of the human model, various sources were cited to obtain average values for the different body parameters. However, key body parameters, such as the circumference of the shoulders, chest and hips were referenced from a study conducted by Pietraszewska and W. Jakubowski [1]. During instances where information on these parameters were unavailable, they were estimated through the golden ratio. The completed model was then meshed through ANSYS Workbench and simulated through an in-house developed code to investigate the amount of passive wave drag experienced at various Froude numbers. These simulations were based on the hybrid method developed by Liu S.K [2] which combines the Rankine source method together with the time domain transient Green function method. These simulations are still in progress and therefore concrete results are not available at the moment. In addition, visualisation tools through MATLAB were explored and tested on existing data on ships so as to facilitate the realisation of the human model results once it is ready.